105k views
2 votes
I how do we simplify-3(4x - 5y + 6) + 8x - 9

2 Answers

3 votes

Answer:

-4x + 15y - 27

Explanation:

-3 (4x -5y + 6) = -3*4x, -3* -5y and -3*6

-3*4x= -12x

-3*-5y= 15y

-3*6= -18

-12x + 15y -18 +8x - 9

Combine like terms (-12x + 8x) and (-18 - 9)

12-8 = 4 and 18+9 = 27 now flip the signs, add the variables back on (the letters) and carry down what was remaining (15y)

-4x + 15y -27

User Chiako
by
5.9k points
2 votes

Explanation:

By using the distributive formula, you can solve this:

-a(b - c + d) = -ab + ac - ad

-3(4x - 5y + 6) + 8x - 9

Use distributive property:

-12x + 15y - 18 + 8x - 9

Add/Subtract by the common terms:

-12x + 8x = -4x

-18 - 9 = - 27

Plug it back into an equation:

= -4x + 15y - 27

That is your answer!!

Hope that helped

~A̷l̷i̷s̷h̷e̷a̷♡

User Roelvogel
by
5.8k points